Applied Micromechanics of Porous Materials - Dormieux, Luc.; Ulm, Franz-Josef.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2005)
Poromechanics is the mechanics of porous materials and is now a well established field in many engineering disciplines, ranging from Civil Engineering, Geophysics, Petroleum Engineering to Bioengineering. However, a rigorous approach that links the physics of the phenomena at stake in porous materials and the macroscopic behaviour is still missing. This book presents such an approach by means of homogenization techniques. Rigorously founded in various theories of micromechanics, these up scaling techniques are developed for the homogenization of transport properties, stiffness and strength properties of porous materials. The special feature of this book is the balance between theory and application, providing the reader with a comprehensive introduction to state-of-the-art homogenization theories and applications to a large range of real life porous materials: concrete, rocks, shales, bones, etc.
Transport properties of porous media -- Transport in Porous Media: Upscaling by Multiscale Asymptotic Expansions -- Micromechanical Analysis of Saturated Porous Media with Local Mass Exchange Phenomenon -- Diffusive transport in disordered media. Application to the determination of the tortuosity and the permeability of cracked materials. -- Microporomechanics -- Poroelasticity and strength of fully or partially saturated porous materials -- Poroelasticity and damage theory for saturated cracked media -- Modeling of Plastic Deformation of Saturated Porous Materials: Effective Stress Concept -- Materials Applications -- Experimental Microporomechanics -- Microelasticity of Bone.
Keywords: Engineering; Mechanics; Mechanics, Applied; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering geology; Engineering—Geology.; Foundations; Hydraulics; Geotechnical engineering; Biophysics; Biological physics; Engineering, general; Solid Mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Geoengineering, Foundations, Hydraulics; Geotechnical Engineering & Applied Earth Sciences; Biological and Medical Physics, Biophysics